HÁBITOS DE USO Y CONSUMO DE LA AUDIENCIA DE LOS MUSEOS. LA ENCRUCIJADA COMUNICATIVA REVELADA - Dr. Félix ORTEGA MOHEDANO,Ddo. Inma GARCÍA MARTÍN,Dra. María Esther PÉREZ PELÁEZ (Fonseca, Journal of Communication, 2023)
At present, the lack of specific regulation and the ambiguity of the Spanish legislation mean that many instagramers do not feel obliged to mention that the content they publish contains adverts. In countries such as the United States and the United Kingdom, this is strongly regulated. Regulation is beginning in Spain via the «Autocontrol de la publicidad» association